Effectiveness of Beetroot Juice Administration on Increasing Hemoglobin Levels in Adolescent Girls with Mild Anemia - Komalasari, Siti Sri; Nency, Aprilya (Journal of Midwifery and Nursing, 2024)
The prevalence of anemia in all age categories in the country is 21.70%. Women are more likely to experience anemia compared to men, with a rate of 23.90% for women compared to 18.40% for men. Based on the place of residence, anemia is more prevalent (22.80%) in rural areas than in urban areas (20.60%), and it is more common (22.70%) in women aged 15 and above. This study aims to determine the effectiveness of beetroot juice administration in increasing hemoglobin levels in adolescent girls with mild anemia in the PMB S working area in 2023. The research method is a case study literature review that measures before and after the intervention, allowing the assessment of effectiveness between the situations before and after the intervention and obtaining a more accurate overview of the intervention results. The results showed that the hemoglobin levels of the respondents increased after receiving the intervention for 7 days with the administration of 100 grams of beetroot juice per day. There was a significant difference in the increase in hemoglobin levels between adolescent girls 1 after receiving beetroot juice and adolescent girls 2 after receiving counseling and health education in adolescents with mild anemia in PMB S Cianjur District in 2023. The difference between the two respondents was quite significant, with respondent 1 showing an increase in Hb levels of 1.1 g/dl, and respondent 2 showing an increase in Hb levels of 1.3 g/dl